CONTENT OF HEAVY METALS LEAD (PB) AND CADMIUM (CD) IN SEDIMENTS IN TANJUNG OYSTER WATERS, SELATAN KONAWE - Afu, La Ode Alirman; Luturmas, Absalom (Journal of Fish Health, 2022)
The waters of Tanjung Tiram Village are one of the places for community coastal area activities, such as ship traffic, ship repair, and the construction of steam power plants that have the potential to cause pollution to the coastal environment so that it can reduce the quality of the environment in the area. This study aims to determine the content of heavy metals lead (Pb) and cadmium (Cd) in the sediment. Sampling was carried out in March 2021 at 4 (four) stations selected by purposive sampling. The samples were analyzed for heavy metal content of Pb and Cd using AAS (Atomic Absorption Spectrophotometry). The results of the analysis of the Pb content in the sediment ranged from 8.7416 to 8.4460 mg/L and the Cd content ranged from 0.3760 to 0.6338 mg/L, exceeding the maximum quality standard set by ANZECC/ARMCANZ.